Upaya Pengembangan Keterampilan Dasar Sains Pada Anak Usia 5-6 Tahun Melalui Pendekatan Kontekstual di PAUD Citra Lestari Sawangan Depok - haryantini haryantini (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Education that is able to support future development is education that is able to develop all the potential of children, so that children can face and be able to solve life problems that they will face. initial assessment or pre-study of basic science skills, children get a minimum score of 20 and a maximum score of 40. Meanwhile, after the action is given in the first cycle, the maximum score obtained increases to 60 and the minimum score is 38. The percentage gain before the action is given is 42.20%, after the action is given in the first cycle increased by 68.38%. This shows that based on the percentage of data it can be seen that in the first cycle the increase obtained is 26.18%. So it can be concluded that the provision of action in the form of a contextual approach in the learning process can develop basic science skills for children aged 5-6 years, especially at PAUD Citra Lestari Sawangan Depok.